Distribution. NE Pacific, Aleutian Is, Gulf of Alaska, and W coast of North America S to C Baja California (Mexico); occasionally to Hawaiian Is and Japan, and into the Bering Sea. in Phocidae - Russell A. Mittermeier; Don E. Wilson (Lynx Edicions, 2014)
Distribution. NE Pacific, Aleutian Is, Gulf of Alaska, and W coast of North America S to C Baja California (Mexico); occasionally to Hawaiian Is and Japan, and into the Bering Sea. Published as part of Russell A. Mittermeier & Don E. Wilson, 2014, Phocidae, pp. 120-183 in Handbook of the Mammals of the World – Volume 4 Sea Mammals, Barcelona :Lynx Edicions on page 170, DOI: 10.5281/zenodo.6607185